A Quantum Leap for Classification: Toward a New Framework for Library Science Beyond Dewey - Kalem, Abderrahmane (The Canadian Journal of Information and Library Science / La Revue canadienne des sciences de l’information et de bibliothéconomie)

(untitled) (Canadian Association for Information Science - Association canadienne des sciences de l'information, 2026)
The classical paradigm of knowledge organization, epitomized by hierarchical systems like Dewey Decimal Classification (DDC), is predicated on a nineteenth-century model of certainty and order. Contemporary scholarship has revealed its inherent limitations, including structural biases, epistemic injustice, and an inability to accommodate the fluid, interdisciplinary nature of modern knowledge. While computational models have increased efficiency, they largely inherit the classical goal of reducing ambiguity to a single, authoritative outcome. This paper argues for a paradigm shift, proposing a novel theoretical framework for classification inspired by the field of quantum cognition. The framework reconceptualizes the information object not as a static entity with intrinsic properties, but as a dynamic system of potential meanings. We adapt three core concepts from quantum theory for library science: Knowledge Superposition to model interdisciplinarity, Semantic Entanglement to provide a formal basis for serendipity, and Observer-Dependent Measurement to address issues of subjectivity and classificatory authority. The viability of this framework is demonstrated through a computational proof-of-concept that simulates how a single, multifaceted document can yield different, probabilistic classifications based on the user’s contextual perspective. This approach offers a robust solution to long-standing challenges, shifting classificatory authority from the institution to the user and providing a path toward transforming the library from a static repository into a dynamic, participatory knowledge system.